Consumer behaviour - Sethna, Zubin (SAGE Publications, 2023)
Informal yet academically rigorous in style, this fun and attractively laid out textbook continues to provide a comprehensive introduction to Consumer Behaviour, drawing on an accessible writing style, engaging examples and a wealth of learning features throughout. The text is balanced in its coverage of both psychological and sociological aspects of consumer behaviour, and examples of consumer behaviour are selected from around the globe, including many of the world's most popular brands and also B2B companies. This new edition has been fully updated to cover the impacts of the Covid-19 pandemic on consumer behaviour as well as the ongoing effects of technology, social media, digitalisation and climate change in adapting consumer behaviours. This textbook is essential reading for all students studying Consumer Behaviour. Zubin Sethna is a Professor of Entrepreneurial Marketing and Consumer Behaviour at Regent's University London.--Back cover